The Influence of Using Online Learning Media on Learning Outcomes of Simulation and Digital Communication for Vocational High School Students - Sumual, Shelty D M; Lumapow, Harol R; Tuerah, Philoteus E A; Tendean, Sherly D; Qowi, Moh; Namsa, Yohanis (JR Education, 2024)
Study This aim is to know the influence use media online learning Edmodo on simulation learning outcomes and digital communication class X student at SMK Negeri 1 Kakas. The population in this study were all students Class X of SMK Negeri 1 Kakas has 92 students. The sample in this research is class X TKJ with 20 students as the experimental class, and class X TKR amount 20 students as the class control. Study This uses an experimental method study Pre-Test, Post-test research type Control Group Design. Method analysis data use test normality Liliefors obtained Fcount = 0.137 And Ftable = 0.19 with level significant 0.05, showing data distribute normal, test Homogeneity use F-test showing sample Which researched obtained Fcount = 1.55 And Ftable = 2.17 based on criteria testing Fcount < Ftable so class experiment And class control Variance Which The same or Homogeneous And test hypothesis use T-test obtained Tcount = 7.13 and Ttable = 2.20 based on the test criteria tcount > ttable shows that the experimental class learning outcomes are greater than the classroom learning outcomes control. Thus it can be concluded that there is an influence of the use of online learning media Edmodo on simulation and communication learning outcomes.